Phenotype‐dependent relationships between cortical macro‐ and micro‐structural neurodegeneration in frontotemporal lobar degeneration. (December 2021) - Placek, Katerina; Anania, Vincenzo; Van Phan, Thanh; de Barros, Nuno Pedrosa; Billiet, Thibo; Ribbens, Annemie; Simen, Arthur; Schwarz, Adam J.
Abstract: Background: Macro‐ and micro‐structural degeneration in cortical grey matter (CGM) accompany the progression of frontotemporal lobar degeneration (FTLD). The former can be measured by brain volumetry from magnetic resonance imaging (MRI) and the latter by mean diffusivity (MD) from diffusion tensor imaging (DTI). While disease‐modifying treatment is expected to slow the progression of both metrics, unexpected treatment effects such as inflammation may alter the relationship between them. Here, we evaluate the cross‐sectional and longitudinal relationships between lobar volume and average MD of CGM in untreated FTLD. Method: 24 patients with behavioral variant frontotemporal dementia (BV), 21 with semantic variant primary progressive aphasia (SV), 20 with nonfluent agrammatic variant primary progressive aphasia (PNFA), and 75 cognitively‐normal controls (CON) from the FTLD Neuroimaging Initiative (FTLDNI) were assessed longitudinally with MRI and DTI. CGM volumes were measured with icobrain dm using T1‐weighted and FLAIR images. CGM MD maps were extracted from DTI and partial‐volume corrected. Volume and average MD were calculated for each lobe using two timepoints approximately 1 year apart, adjusted for age and sex, and z‐scored relative to CON. For each lobe, multiple linear regression models with Bonferroni correction assessed the effect of FTLD phenotype on the relationship between 1) baseline MD and volume, and 2) percent change from baseline in MD and volume. Result: At baseline, BV, SV, and PNFA demonstrated significantly more negative associations between MD and volume in the frontal lobes relative to CON (all p values <.05), such that greater MD related to lesser volume in each phenotype. Significantly more negative associations between MD and volume relative to CON were observed for BV and SV in the temporal lobe, and for PNFA in the parietal lobe ( p <.05). For percent change from baseline, BV demonstrated a significantly more negative association between MD and volume in the frontal and parietal lobes relative to CON ( p <.05), such that percent increase in MD related to percent decrease in volume. Conclusion: Our results elucidate phenotypic differences in cortical macro‐ and micro‐structural degeneration in FTLD and provide a novel frame of reference for MRI and DTI for interventional clinical trials.